Evaluation of blood pressure in feline night monkeys (Aotus azarae infulatus) under different restraint protocols. Issue 6 (29th July 2015) - Chaves, Rosa Helena de Figueiredo; Souza, Nazaré Fonseca de; Imbeloni, Aline Amaral; Neves, Ana Cláudia de Souza; Teixeira, Renan Kleber Costa; Santos, Camila de Cassia dos
Abstract: Background: Feline night monkeys are very susceptible to stress when handled, and because of that, the use of anesthetic and physical restraint methods should be carefully evaluated. To ensure a safer anesthesia to the animals the present study aimed to observe the influence of four restraint protocols in the blood pressure of Aotus azarae infulatus. Methods: Blood pressure was obtained from 10 animals subjected to restraining protocols using tiletamine and zolazepam, isoflurane, ketamine and midazolam, and physical restraint and results were evaluated to determine their effect on this exam. Results: Among the restraint protocols tested, the anesthetic isoflurane promoted lower blood pressure values and no differences were observed between values measured in both arms in all groups. Conclusion: The results of our study suggest that all restraint protocols tested significantly alter blood pressure in this species of primates.